Application of SDOC Cut Points for Low Muscle Strength for Recovery of Walking Speed After Hip Fracture - Orwig, Denise L (J Gerontol A Biol Sci Med Sci, 2020)
BACKGROUND: Sarcopenia is often conceptualized as a precursor to loss of mobility, but its effect on recovery of mobility after a hip fracture is unknown. We determined the prevalence of low muscle strength (weakness) after hip fracture using putative sarcopenia metrics (absolute grip strength, and grip strength normalized to body mass index, total body fat, arm lean mass, and weight) identified by the Sarcopenia Definitions and Outcomes Consortium (SDOC). METHODS: We examined two well-characterized hip fracture cohorts of community-dwelling older adults from the Baltimore Hip Studies (BHS). The prevalence of muscle weakness was assessed using the SDOC cut points compared to published definitions at 2 and 6 months postfracture. We assessed associations of 2-month weakness with 6-month walking speed <0.6 m/s and calculated the sensitivity and specificity in predicting lack of meaningful change in walking speed (change < 0.1 m/s) at 6 months. RESULTS: Two hundred and forty-six participants (192 women; 54 men) were included; mean (SD) age of 81 (8) for women and 78 (7) for men. At 2 months, 91% women and 78% men exhibited slow walking speed (< 0.6 m/s). SDOC grip strength standardized by weight (<0.34 kg women, <0.45 kg men) was the most prevalent measure of weakness in men (74%) and women (79%) and provided high sensitivity in men (86%) and women (84%) predicting lack of meaningful change in walking speed at 6 months, although specificity was poor to moderate. CONCLUSIONS: SDOC cut points for grip strength standardized to weight provided consistent indication of poor walking speed performance post-hip fracture.